Exploratory study : the role of leadership in the sustainability of social enterprises (Singapore). - Ho, Fung-Min. (2011)
The purpose of this exploratory study is to expand the field of social enterprise research to include a focus on the role of leadership in sustainability. This study uses a qualitative approach, sampling leaders from social enterprises and using a structured interview to uncover their leadership practices related to sustainability. The leaders we interviewed adopted similar definitions as to what defined a social enterprise. For sustainability, leaders also established that the financial bottom-line of the social enterprise needs to be met before the social goals can be achieved. They undertook various business strategies that are comparative of others in the marketplace. To ensure sustainability, beneficiaries were carefully selected with regard to their suitability for training. One of the main ways that leaders coped to overcome the challenge of customers‟ expectations was through educating them about social enterprises. Many of the respondents also made an effort to learn from mistakes as they embarked on this journey. This study will be useful in aiding aspiring social entrepreneurs in Singapore regarding the aspects of leadership required for sustaining social enterprises. Current leaders of social enterprises can also glean insights from this study, to help them to work towards the sustainability of their enterprise. However, since the social enterprise industry in Singapore is still in its nascent stage, there were some initial difficulties in deciding which enterprises could be labeled as „sustainable‟.